2021
DOI: 10.1021/acsami.0c21612
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controlled Spalling of LaAlO3/SrTiO3 Micromembranes

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…c) Top panel reproduced with permission. [ 16 ] Copyright 2021, American Chemical Society. Bottom two panels reproduced with permission.…”
Section: Fabrication Of Single‐crystal Freestanding Thin Filmsmentioning
confidence: 99%
See 4 more Smart Citations
“…c) Top panel reproduced with permission. [ 16 ] Copyright 2021, American Chemical Society. Bottom two panels reproduced with permission.…”
Section: Fabrication Of Single‐crystal Freestanding Thin Filmsmentioning
confidence: 99%
“…As expected for the spalling process, the parallel fracture occurred below the tensile LAO and each membrane contains an LAO/STO interface. Dahm et al [ 16 ] showed that by pre‐patterning of the growth substrate using lithography and ion milling, the lateral locations of cracks can be controlled. This procedure enabled the controlled formation of free‐standing LAO/STO micro membranes with sizes from 2 to 20 µm.…”
Section: Fabrication Of Single‐crystal Freestanding Thin Filmsmentioning
confidence: 99%
See 3 more Smart Citations